Performance in Greek and Roman theatre - Harrison, George William Mallory.; Liapēs, Vaios. (Mnemosyne, Supplements, 2013)
In recent years, classicists have begun aggressively to explore the impact of performance on the ways in which Greek and Roman plays are constructed and appreciated, both in their original performance context and in reperformances down to the present day. While never losing sight of the playscripts, it is necessary to adopt a more inclusive point of view, one integrating insights from archaeology, art, history, performance theory, theatre semiotics, theatrical praxis, and modern performance reception. This volume contributes to the restoration of a much-needed balance between performance and text: it is devoted to exploring how performance-related considerations (including stage business, masks, costumes, props, performance space, and stage-sets) help us attain an enhanced appreciation of ancient theatre.